Effect of Incorporation of Potato Dried Powder on the Quality Characteristics of Spent Broiler Breeder Hen Chicken Koftas - Sharada, M. V. Sneha; Indumathi, J.; Reddy, G. V. Bhaskar; Shakila, S.; Mouli, A. Chandra (International Journal of Bio-resource and Stress Management, 2025)
The present study was carried out during July-October, 2022 in Department of Livestock Products Technology, College of Veterinary Science, Tirupati, Andhra Pradesh, India to evaluate the effect of different levels of potato dried powder on the quality characteristics of chicken koftas. The potato dried powder was incorporated at three different levels viz. 2, 4 and 6% in the formulation. The products were analyzed for various physicochemical (pH, emulsion stability, cooking yield, water holding capacity, proximate analysis) and sensory attributes. pH, emulsion stability, cooking yield, water holding capacity, moisture and crude fibre content of the products showed significant (p<0.05) increasing trend with increase in levels of incorporation of potato dried powder. However, a significant (p<0.05) decrease in the crude protein, ether extract and ash content of the chicken koftas was observed with increasing levels of incorporation. However, 4% potato dried powder incorporated spent broiler breeder hen chicken koftas scored significantly (p<0.05) better for all sensory attributes such as appearance, flavour, juiciness, texture and overall acceptability. Spent broiler breeder hen chicken koftas incorporated with 6 and 2% level of vegetable dried powders scored significantly (p<0.05) lower scores for all sensory attributes than 4% level of incorporation. Hence incorporation of potato dried powder at 4% level in chicken koftas was considered to be optimum.